Effects of neuropeptide Y on electrical activity and myocardial contractility - A.A. Zverev; T.A. Anikina; N.G. Iskakov; A.V. Krulova; P.M. Masliukov; J.P. Timmermans; T.L. Zefirov (Учёные записки Казанского университета: Серия Естественные науки)
Neuropeptide Y (NPY) and agonist Leu(31)Pro(34)NPY were used to determine the type of NPY receptors involved in electrical activity and myocardial contraction. The experiments on the electrical activity of the right atrium showed that NPY and the selective agonist had negative inotropic and chronotropic actions through the activation of NPY1 receptor. The activation of NPY-receptors of right atrial cardiomyocytes with NPY leads to a change of the membrane potential and the amplitude-time parameters of the action potential. The experiments with the myocardial strips showed that NPY and the agonist produced the most potent effect at a concentration of 10–7 M. At this concentration, Leu(31)Pro(34)NPY showed the greatest positive inotropic effect on the contraction of the atria and ventricles.